2017
DOI: 10.1002/cncy.21931
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemistry for SOX‐11 and TFE3 as diagnostic markers for solid pseudopapillary neoplasms of the pancreas in FNA biopsies

Abstract: SOX-11 is a sensitive and specific immunocytochemical stain for SPNs in EUS-FNA specimens, and it may be useful as a diagnostic marker for distinguishing SPNs from its cytologic mimics. Cancer Cytopathol 2017;125:831-7. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 22 publications
2
33
0
2
Order By: Relevance
“…Recently, after extensive molecular characterization of SPNs, multiple authors have identified additional IHC stains that are useful in the identification of SPNs . These IHC stains include lymphoid enhancer‐binding factor 1 (LEF1) and androgen receptor (AR), in addition to transcription factor binding to IGHM enhancer 3 ( TFE3 ) and SRY‐box 11 (SOX11) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, after extensive molecular characterization of SPNs, multiple authors have identified additional IHC stains that are useful in the identification of SPNs . These IHC stains include lymphoid enhancer‐binding factor 1 (LEF1) and androgen receptor (AR), in addition to transcription factor binding to IGHM enhancer 3 ( TFE3 ) and SRY‐box 11 (SOX11) .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, after extensive molecular characterization of SPNs, multiple authors have identified additional IHC stains that are useful in the identification of SPNs . These IHC stains include lymphoid enhancer‐binding factor 1 (LEF1) and androgen receptor (AR), in addition to transcription factor binding to IGHM enhancer 3 ( TFE3 ) and SRY‐box 11 (SOX11) . Although the surgical pathology literature has reported that strong and diffuse nuclear positivity for LEF1 and AR is frequent in SPN surgical resection specimens (frequency of 93.4% and 81.5%, respectively), to our knowledge no study to date has evaluated the usefulness of these markers on cytology specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Although the aspecific NSE is usually positive, but the chromogranin-A or synaptophysin are negative, moreover, no hormonal activity is identified in this tumor. The nuclear expression of βcatenin, SOX-11 and TFE3 positivities are characteristic findings in SPN [71], but not in PNET and in acinar cell carcinoma (Fig. 2i).…”
Section: Important Practical Pathological Considerationsmentioning
confidence: 92%
“…In case of diagnostic uncertainty, EUSguided fine needle aspiration is recommended, which plays an important role in providing accurate and reliable preoperative cytological diagnosis (61,62,63). Papavramidis and Papavramidis (49) include CT-guided FNA in the SPN diagnostic algorithm.…”
Section: Magnetic Resonance Imaging (Mri) Is the Diagnostic Methods Ofmentioning
confidence: 99%